Temps dip deeper: Temporary employment and the midlife nadir in human well-being - Alan T. Piper (Freie Universität Berlin, School of Business & Economics, 2020)
Temporary employees rank lower than permanent employees on various measures of mental and physical health, including well-being. In parallel, much research has shown that the relationship between age and well-being traces an approximate U-shape, with a nadir in midlife. Temporary employment may well have different associations with well-being across the lifespan, likely harming people in midlife more than at the start of their working lives. Using over twenty years of the German Socio-economic panel (SOEP), this investigation considers the relationship between temporary employment, age and well-being. In doing so, it both sheds new light on the relationship between temporary employment and well-being, and explores a reason for the oft-found U-shaped relationship between age and well-being. The results show that temporary employment deepens the U-shape in midlife, and that this result holds when many socioeconomic factors as well as the industry, region, cohort, personality, employment security and job worries are taken into account. Furthermore, the investigation considers transitions between permanent and temporary employment and uses these to assess causation and selection.
urn:nbn:de:kobv:188-refubium-28410-9
Keywords: I31; J41; 330; temporary employment; permanent employment; age; life satisfaction; SOEP